Experimental Study Regarding Variation of Force in Inverse Extrusion Using Active Friction. (2015) - Socaciu, Teodor
Abstract: In the inverse extrusion, big friction forces rise between the tool and the semi - product, which worsen a great deal the parameters of the material's plastic deformation process. In order to diminish the unwanted effect of friction in the extrusion processing, the authors have conceived a special and an original equipment, with whose help the friction force is acting towards the active one. The paper presents experimental research regarding the ways of improving the inverse extrusion process parameters, under the conditions of using respective equipment.